ANALISYS OF STRESS CAUSED BY THE INFLUENCE OF CIRCULARITY ERROR IN PRESSURE VESSEL - Souza, Ivair Carvalho de; Fioravante, André; Carneiro, José Rubens Gonçalves; Carneiro, João Pedro Santiago (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The quality of pressure vessels’ manufacturing process in terms of their circularity error is a theme of discussion due to there is a difference between acceptance criteria of two most utilized standards in Brazil, that regulates manufacturing of this equipment. The stresses caused by circularity error in a pressure vessel were simulated using the finit element method, the software were COSMOSWorks and results obtained were compared to the acceptance criteria of each standard. The objective of this work is to evaluate the impact of pressure vessel’s circularity error and compare the results to N-268 e ASME VIII D.1 standards.